Angle dependent molecular dynamics simulation of flux pinning in YBCO superconductors with artificial pinning sites. (12th July 2018) - Paturi, P; Malmivirta, M; Hynninen, T; Huhtinen, H
Abstract: A molecular dynamics (MD) simulation to simulate the vortices in superconductors with artificial pinning sites is presented. The simulation reproduces the correct anisotropic behavior in angular dependence of critical current. We also show that the shape of the curve depends on the size of the pinning sites and the change from p = 0.5 to is due to the breaking of the vortex lattice to individually acting vortices. The results beautifully correspond to experimental data. Furthermore, we found that the size and shape of the c -axis peak observed with columnar pinning sites in also depends on the size of the rods, larger pinning sites leading to wider peaks. The results obtained from the MD-simulation are similar to those of the much more computationally intensive Ginzburg–Landau simulations. Furthermore, the MD-simulations can provide insight to the vortex dynamics within the samples.